1997
DOI: 10.1016/s0014-5793(97)00952-6
|View full text |Cite
|
Sign up to set email alerts
|

Chinese hamster protein homologous to human putative protein kinase KIAA0204 is associated with nuclei, microtubules and centrosomes in CHO‐K1 cells

Abstract: Monoclonal antibody raised against a preparation of loach fish sperm centrosomes was used for screening of cDNA expressing library of Chinese hamster CHO-K1 cells. Two positive clones appeared to encode 628 amino acid protein fragment that was 72% identical to human KIAA0204 protein, i.e. putative protein kinase. Polyclonal antibodies raised against products of cDNA expression in E. coli recognized 210-kDa polypeptide in CHO-K1 cells and immunostained nuclear speckles, centrosomes and microtubules in these cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In our previous work we have shown that the protein kinase LOSK was associated with microtubules and centrosome in CHO-K1 cell culture and in fish sperm (Zinovkina et al, 1997(Zinovkina et al, , 1998Nadezhdina et al, 2001). We proved it with immunofluorescence staining, immunoelectron microscopy, and cosedimentation with microtubules.…”
Section: Full-length Losk Partially Colocalizes With Microtubules Whmentioning
confidence: 60%
See 3 more Smart Citations
“…In our previous work we have shown that the protein kinase LOSK was associated with microtubules and centrosome in CHO-K1 cell culture and in fish sperm (Zinovkina et al, 1997(Zinovkina et al, , 1998Nadezhdina et al, 2001). We proved it with immunofluorescence staining, immunoelectron microscopy, and cosedimentation with microtubules.…”
Section: Full-length Losk Partially Colocalizes With Microtubules Whmentioning
confidence: 60%
“…LOSK distributed mostly in cytoplasm is not a specific centrosomal protein. However, it was found in isolated sperm basal bodies and in centrosomes in cell culture (Zinovkina et al, 1997;Nadezhdina et al, 2001). Among potential centrosomal targets of LOSK (probably indirect) the tempting one is dynactin that localizes both in centrosomes and in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the kidney SLK is found in tubular and glomerular epithelial cells (GECs; podocytes) 2 (10). Subcellularly, SLK is localized in the cytosol, nucleus, microtubules, and centrosomes (11,12). The regulation and functions of SLK have received considerable attention in recent years.…”
mentioning
confidence: 99%